1998
DOI: 10.3109/03008209809002445
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Distinct Metabolic Pools of Aggrecan and Their Relationship to Type VI Collagen in the Chondrons of Mature Bovine Articular Cartilage Explants

Abstract: The metabolism and distribution of newly synthesized aggrecan present in the extracellular matrix of intact explant cultures of mature articular cartilage was investigated with respect to type VI collagen-stained chondrons. Using biochemical, autoradiographical and novel confocal immunohistochemical techniques it was shown that aggrecan exists as a number of distinct pools that are located within the extracellular matrix of the tissue. The first was identified as a pool of high specific radioactivity, much of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…3), were consistent with previous observations of bovine cartilage 14,20 and around human chondrocytes. 21 The pericellular matrix (within ,2 mm of the cell membrane) exhibited the most rapid rates of PG deposition, which decreased nearly monotonically with increasing distance from chondrocytes regardless of experimental conditions (Fig.…”
Section: Resultssupporting
confidence: 93%
“…3), were consistent with previous observations of bovine cartilage 14,20 and around human chondrocytes. 21 The pericellular matrix (within ,2 mm of the cell membrane) exhibited the most rapid rates of PG deposition, which decreased nearly monotonically with increasing distance from chondrocytes regardless of experimental conditions (Fig.…”
Section: Resultssupporting
confidence: 93%
“…These findings are consistent with studies using other joint connective tissues such as articular cartilage [15] and collateral ligament [10]. In the case of articular cartilage, it has been shown that the majority of newly synthesized aggrecan remains closely associated with the chondrocytes [16,17]. However, the majority of the chemical pool of aggrecan resides in the interterritorial matrix and it is this population that is responsible for the biomechanical properties of cartilage.…”
Section: Discussionsupporting
confidence: 89%
“…It forms a “cargo‐net like” organization around each chondrocyte in vitro (29) . In addition, type IX collagen, type II collagen, and aggrecan have been identified as components of pericellular matrix (30–32) . However, it is not known how these various molecules, which include both collagens and proteoglycans, form a pericellular matrix network.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the role of pericellular matrix molecules was studied by correlating the presence of a particular matrix molecule to its function after enzymatic or mechanical isolation of chondrons (8,32) . Alteration of the content of pericellular matrix molecules such as type VI collagen was also achieved by treatment of chondrocytes with cytokines including IL‐1 (30) . However, such studies were correlative in nature, because the contents of multiple matrix molecules and matrix degradation enzymes may be altered simultaneously by such treatment.…”
Section: Discussionmentioning
confidence: 99%